Evaluation of Climate Change Impacts on Lettuce Hydroponic UMKM (Case Study of Alam Tani Hidrofarm Kudus) - Delbi Rizka Adik Azhari; Riyan Andni (Journal of Social Science Utilizing Technology, 2023)
Background. Changes in climate have a significant impact on various aspects of work, especially in the modern agricultural sector. Therefore, the UMKM sector of Alam Tani Hidrofarm Kudus is facing new challenges such as in the production process. Purpose. This study aims to describe, explain and evaluate the effect of climate change on the growth of vegetable crops in the UMKM Alam Tani Hidrofarm Kudus. Method. The research method used is a qualitative approach with a case study approach. Data were obtained through observation, in-depth interviews, and data and document collection. Results. The results showed that climate change resulted in various impacts such as decreased productivity and quality in hydroponic lettuce crops. Factors such as temperature extremes, changes in rainfall, humidity, diseases and pests, plant nutrients, environment, variety and technology used. However, this study also identified various evaluations to improve the productivity and quality of hydroponic lettuce crops. These solutions include regular irrigation systems, greenhouses, variety selection, proper nutrient utilisation, monitoring, the use of smart technology, and the use of temporary protection. Conclusion. Temperature variations and unpredictable rainfall patterns can disrupt the balance of the hydroponic environment resulting in slowed growth and reduced crop quality. These factors can undermine food security and the sustainability of cultivation. In addition, this research underscores the need for strategic adaptation, such as the use of climate control technologies, selection of climate-resilient varieties, and efficient water management. Facing the challenges of climate change in the context of hydroponic farming requires an integrated approach involving various parties, including farmers, researchers, and policy makers to ensure a stable and sustainable food supply.